The potential of copper oxide nanoparticles photocatalyst and microalgae for leachate treatment - Liang, Yan Peng (2025)
The Municipal Solid Waste landfill has become a big challenge to the world nowadays. The percolating wastewater that comes out from this waste material, also known as leachate, is highly toxic and contaminated. Leachate contains high suspended solids, heavy metals and others hazardous substances such as xenobiotic compounds, ammonia, volatile organic compounds, hydrogen sulfide, methane and others. The objective of this research is to determine the effectiveness and efficiency of integrated methods using green synthesized nanoparticles and phyco-remediation using microalgae to treat leachate. In this study, the pre-treated leachate samples were treated with heterogenous photocatalytic degradation, under different concentrations of 100 mg, 150 mg and 200 mg of copper oxide nanoparticles (CuO NPs). The leachate samples were further polished using microalgae species known as Chlorella vulgaris. Microalgae were cultivated and grown in different percentages of 0%, 25%, 50%, 75% and 100% of photo-treated leachate samples for seven (7) days. The water analysis for before and after treatment was carried out according to standard methods. Parameters such as pH, Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), Suspended Solids (SS), Ammoniacal Nitrogen (AN) were tested. Throughout this research, the mentioned integrated leachate treatment had achieved the total removal rate of 98% of COD, 99% of BOD5, 93% of SS and 93% of AN. As a conclusion, the integrated system of nanoparticles and microalgae has shown the optimization of leachate treatment by achieving the most satisfactory reduction rate in the tested parameters.